A rare variant in EZH2 is associated with prostate cancer risk. Issue 5 (12th April 2021) - Raspin, Kelsie; FitzGerald, Liesel M.; Marthick, James R.; Field, Matt A.; Malley, Roslyn C.; Banks, Annette; Donovan, Shaun; Thomson, Russell J.; Foley, Georgea R.; Stanford, Janet L.; Dickinson, Joanne L.
Abstract: Prostate cancer (PrCa) is highly heritable, and although rare variants contribute significantly to PrCa risk, few have been identified to date. Herein, whole‐genome sequencing was performed in a large PrCa family featuring multiple affected relatives spanning several generations. A rare, predicted splice site EZH2 variant, rs78589034 (G > A), was identified as segregating with disease in all but two individuals in the family, one of whom was affected with lymphoma and bowel cancer and a female relative. This variant was significantly associated with disease risk in combined familial and sporadic PrCa datasets (n = 1551; odds ratio [OR] = 3.55, P  = 1.20 × 10 −5 ). Transcriptome analysis was performed on prostate tumour needle biopsies available for two rare variant carriers and two wild‐type cases. Although no allele‐dependent differences were detected in EZH2 transcripts, a distinct differential gene expression signature was observed when comparing prostate tissue from the rare variant carriers with the wild‐type samples. The gene expression signature comprised known downstream targets of EZH2 and included the top‐ranked genes, DUSP1, FOS, JUNB and EGR1, which were subsequently validated by qPCR. These data provide evidence that rs78589034 is associated with increased PrCa risk in Tasmanian men and further, that this variant may be associated with perturbed EZH2 function in prostate tissue. Disrupted EZH2 function is a driver of tumourigenesis in several cancers, including prostate, and is of significant interest as a therapeutic target. Abstract : What's new? Prostate cancer has high heritability, yet few risk variants have been identified. Here, the authors went looking for rare variants using whole genome sequencing (WGS). They tested three members of a large, multigenerational Tasmanian family with a high proportion of prostate cancer cases. WGS turned up a rare variant in EZH2, a gene that has previously been associated with prostate tumorigenesis. The researchers found the variant was associated with PrCa both in familial and sporadic cases. Tumor analysis suggests that the mutation disrupts EZH2 function and alters the expression of downstream targets.